The quality of life in girls with Rett syndrome - Lucia Parisi; Teresa Di Filippo; Michele Roccella (Mental Illness)
Nowadays, quality of life is receiving an increasing attention in all scientific areas. Rett syndrome (RTT) is a rare neurological development, affecting mainly females. The congenital disease affects the central nervous system, and is one of the most common causes of severe intellectual disability. The aim of our study is to evaluate the effect of RTT on the quality of life of people who are affected. Both parents of 18 subjects, all female, diagnosed with RTT, took part in the research. Quality of life was assessed using the Italian version of the Impact of Childhood Illness Scale. This scale consists of 30 questions that investigate the effect of illness on children, parents and families. For each question, the parent was asked to rate two variables: frequency and importance. Another questionnaire was administered to obtain medical history, diagnostic and therapeutic data of the persons with RTT. Our data show that RTT has a considerable impact on both the child’s development and the entire family. Parents’ answers demonstrated that their child’s illness had consequences for the child and how the family coped with it. For this reason, attention should be directed at psychological and social aspects, as well as attitudes, manners, reactions and effects such disturbances can have on the entire family.